Is a hilly neighborhood environment associated with diabetes mellitus among older people? Results from the JAGES 2010 study. (June 2017) - Fujiwara, Takeo; Takamoto, Iseki; Amemiya, Airi; Hanazato, Masamichi; Suzuki, Norimichi; Nagamine, Yuiko; Sasaki, Yuri; Tani, Yukako; Yazawa, Aki; Inoue, Yosuke; Shirai, Kokoro; Shobugawa, Yugo; et al.
Abstract: Background: Although living in a hilly environment may promote muscular activity in the daily lives of residents, and such activity may prevent diabetes mellitus, few studies have focused on the impact of living in a hilly environment on diabetes mellitus. The purpose of this study was to investigate the impact of a hilly neighborhood environment on DM in older people. Methods: We used data from the Japan Gerontological Evaluation Study, a population-based, cross-sectional study of individuals aged 65 or older without long-term care needs in Japan, which was conducted in 2010. A total of 8904 participants in 46 neighborhoods had responded to the questionnaire and undergone a health check. Diabetes mellitus was diagnosed as HbA1c  ≥ 6.5% and those undergoing treatment for diabetes mellitus. Poorly controlled diabetes mellitus was diagnosed in those without other chronic diseases who had an HbA1c > 7.5%, and in those with other chronic diseases if their HbA1c was >8.0%. Neighborhood environment was evaluated based on the percentage of positive responses in the questionnaire and geographical information system data. A multilevel analysis was performed, adjusted for individual-level risk factors. Furthermore, sensitivity analysis was conducted for those who were undergoing treatment for diabetes mellitus (n = 1007). Results: After adjustment for other physical environmental and individual covariates, a 1 interquartile range increase (1.48°) in slope in the neighborhood decreased the risk of poorly controlled diabetes mellitus by 18% (odds ratio [OR]: 0.82, 95% confidence interval [CI]: 0.70–0.97). Sensitivity analysis confirmed that larger slopes in the neighborhood showed a significant protective effect against diabetes mellitus among those who were undergoing treatment for diabetes mellitus (OR: 0.73, 95% CI: 0.59–0.90). Conclusion: A hilly neighborhood environment was not associated with diabetes mellitus, but was protective against poorly controlled diabetes mellitus. Highlights: A hilly neighborhood environment was not associated with DM. However, larger slopes environment decreased the risk of poorly controlled DM. The protective effect was confirmed among participants undergoing treatment for DM.